Pengembangan Bahan Ajar Dasar Tata Rias Wajah untuk Mahasiswa Prodi Pendidikan Vokasional Kesejahteraan Keluarga (PVKK) Tata Rias - Aprillia Evi Mursanti; Achmad Noor Fatirul; Hartono (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2020)
The quality of good learning is supported by good literature. By this teaching material that have been validated by the experts, the learning process will be better. The research method is a development model of 4D. The results obtained from SME (Cosmetology Experts) stated that the feasibility of the teaching materials in the PVKK Study Program, the average is 88% (very good/proper category). Validation results for design experts an average of 83% (good/decent category), while for the results of the assessment of the lecturer of the PVPK Study Program rated 98%, which is interpreted in the excellent category. While the test in small groups is 84.1%, which means good (feasible), and the large group test is 86.15%, which means very good (feasible). Thus the basic teaching materials for cosmetology can support cosmetology learning to run well and smoothly.